Potencial evocado auditivo de tronco encefálico – tone burst e resposta auditiva de estado estável em lactentes - Porto, Maria Angelica de Almeida [UNIFESP] (2009)
Introduction: Audiological diagnosis in the first weeks or months of life has increased with the consolidation of newborn hearing screening programs. Otoacoustic emissions (OAE) and auditory brainstem response (ABR) with click stimuli are widely used for this purpose. For a successful early intervention, accurate information about type, degree, and configuration of hearing loss are necessary. ABR with tone burst stimuli (TB ABR) and auditory steady-state response (ASSR) exams have been of great value, since these tests provide specific frequency information, resulting in a more detailed hearing evaluation. Objective: Analyze the clinical applicability of TB ABR and ASSR at 2 kHz, in full-term and premature infants. Method: The study was conducted at UNIFESP. Subjects were consisted of 17 premature infants and 19 full-term infants, male and female. In natural sleep, they have undergone TB ABR and ASSR exams (Smart EP - Intelligent Hearing Systems), at 2000 Hz. Results: Right and left ears responses showed no statistically significant differences, therefore they were considered as a whole. Wave V mean latencies in TB ABR were 7.9 ms to 80 dBnHL, 8.9 ms to 60 dBnHL, 9.9 ms to 40 dBnHL and 10.8 ms to 30 dBnHL. Electrophysiological minimum response obtained with TB ABR was 32.4 dBnHL (52.4 dBSPL), on average. ASSR minimum response was 13.8 dBHL (26.4 dBSPL), on average. TB ABR and ASSR exams lasted 21.1 min and 22 min, respectively. Premature and full-term infants responses showed no statistically significant differences, except for ASSR duration. Conclusions: Both TB ABR and ASSR have clinical applicability at 2 kHz in infants, with no differences between premature and full-term individuals.